Improving Teachers' Professional Competence through Technology-Based Training in Realizing Innovative Learning Strategies - Eliaser Sinlae, Dominggus; Pakartiar, Georgius Braminta; Warata, Matilda Indriani Umbu; Kabnani, Olpi; Boimau, Oma Selfiadi (Universitas Pahlawan Tuanku Tambusai, 2025)
Education is a strategic process to improve the quality of human resources to be able to compete globally. In Indonesia, the challenges of equalizing and improving the quality of education are very complex, especially due to diverse geographical conditions. One of the main factors determining the success of education is teacher competence, which includes pedagogical, professional, personality, and social aspects. Along with technological advances, there are great opportunities to improve the quality of learning through the use of educational technology. This study aims to analyze efforts to improve teacher professional competence through training and the use of technology in realizing innovative learning. The method used is a literature study with data collection techniques through written sources such as books, journals, scientific articles. The results of this literature study show that structured and ongoing training on the use of technology, such as digital learning platforms and interactive media, has a positive impact on improving teacher teaching skills. Teachers become more creative in designing relevant and interesting learning experiences for students. In conclusion, technology-based training has a significant contribution to improving teacher professional competence and encouraging the creation of innovative learning that is adaptive to the needs of the times.